2017
DOI: 10.1016/j.advwatres.2017.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Impact of type of salt and ambient conditions on saline water evaporation from porous media

Abstract: HIghlights• Evaporation from porous media saturated with different salt solutions was investigated • Effects of ambient temperature, relative humidity and type of salt were discussed • Salt precipitation does not necessarily limit the evaporative flux • Strong direct correlation between evaporation and surface salt precipitation was found AbstractSaline water evaporation from porous media is important in many processes such as soil salinization, CO 2 sequestration, crop production and water management. This p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(44 citation statements)
references
References 35 publications
1
40
1
Order By: Relevance
“…The exact location of nucleation centers, their spatial density, and rate of formation may be affected by various parameters such as evaporation rates and humidity (Desarnaud et al, 2015;Shokri-Kuehni, Norouzi, et al, 2017), porous media grain and pore dimensions (Norouzi Rad et al, 2013;Zehnder & Arnold, 1989) and distribution Nachshon, Shahraeeni, et al, 2011), grain angularity (Norouzi & Shokri, 2014), and solute concentrations (Bergstad et al, 2017). Nevertheless, the rate of ESC formation and its upward growth varied between the different soils.…”
Section: Discussionmentioning
confidence: 99%
“…The exact location of nucleation centers, their spatial density, and rate of formation may be affected by various parameters such as evaporation rates and humidity (Desarnaud et al, 2015;Shokri-Kuehni, Norouzi, et al, 2017), porous media grain and pore dimensions (Norouzi Rad et al, 2013;Zehnder & Arnold, 1989) and distribution Nachshon, Shahraeeni, et al, 2011), grain angularity (Norouzi & Shokri, 2014), and solute concentrations (Bergstad et al, 2017). Nevertheless, the rate of ESC formation and its upward growth varied between the different soils.…”
Section: Discussionmentioning
confidence: 99%
“…Evaporation of saline water from porous media is important in many environmental, engineering, and hydrological processes including vegetation and plant growth, soil salinization, land-atmosphere interaction, functioning of the ecosystem, and crop production [Rodriguez-Navarro and Doehne, 1999;Suweis et al, 2010;Ott et al, 2015;Bergstad and Shokri, 2016]. This has motivated many researchers to investigate various aspects of this process including the effects of grain size, wettability, heterogeneity, and external conditions [Huinink et al, 2002;Guglielmini et al, 2008;Nachshon et al, 2011aNachshon et al, , 2011bEloukabi et al, 2013;Norouzi Rad et al, 2015;Jambhekar et al, 2015;Börnhorst et al, 2016;Dai et al, 2016;Shokri-Kuehni et al, 2017].…”
Section: Introductionmentioning
confidence: 99%
“…Saline water evaporation is influenced by transport properties of the porous media, properties of the evaporating solution, external conditions (wind, radiation, ambient temperature, and relative humidity), and precipitation of salt crystals [Norouzi Rad et al, 2013;Shokri, 2014;Jambhekar et al, 2015;Shokri-Kuehni et al, 2017]. During evaporation, solute is transported, via capillary-induced liquid flow, from a wet zone to the evaporation surface resulting in increasing solute concentration close to the vaporization plane [Guglielmini et al, 2008].…”
Section: Introductionmentioning
confidence: 99%
“…This invasion of salt solutions is eventually followed by drying and concomitant crystallization of the dissolved salts. The latter significantly influence the drying kinetics of porous structures, and previous studies have reported counterintuitive trends in drying kinetics when salts are present B Mohsin J. Qazi m.j.qazi@uva.nl 1 Institute of Physics, University of Amsterdam, Science Park 904, 1098 XH Amsterdam, The Netherlands (Veran-Tissoires et al 2012;Desarnaud et al 2015;Shokri-Kuehni et al 2017;Bergstad and Shokri 2016;Bergstad et al 2017). Depending on the environmental conditions, the salt precipitation can alter the drying process by forming a salt crust that blocks the evaporation from the core of the stones (Desarnaud et al 2015;Gupta et al 2014;Grementieri et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…This often happens at low relative humidity, where the initial drying is rapid. On the other hand, for drying at higher relative humidity, different salt precipitation dynamics at the surface enables continuous hydraulic conductivity and can even enhance the evaporation process (Desarnaud et al 2015;Gupta et al 2014;Shokri-Kuehni et al 2017;Veran-Tissoires et al 2012). This then leads to the counterintuitive result that the total drying time can be longer at a low relative humidity.…”
Section: Introductionmentioning
confidence: 99%